If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(y + -7) + 12y = 16 + -70 Reorder the terms: 14(-7 + y) + 12y = 16 + -70 (-7 * 14 + y * 14) + 12y = 16 + -70 (-98 + 14y) + 12y = 16 + -70 Combine like terms: 14y + 12y = 26y -98 + 26y = 16 + -70 Combine like terms: 16 + -70 = -54 -98 + 26y = -54 Solving -98 + 26y = -54 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '98' to each side of the equation. -98 + 98 + 26y = -54 + 98 Combine like terms: -98 + 98 = 0 0 + 26y = -54 + 98 26y = -54 + 98 Combine like terms: -54 + 98 = 44 26y = 44 Divide each side by '26'. y = 1.692307692 Simplifying y = 1.692307692
| 6+2(7x+2)=3 | | 5y=4x+12 | | -3x+3=5x-5 | | (3a+4b)(3a-4b)= | | x*1+3*1,5+(x-3)*2=19,5 | | 3x+37=97 | | x^2-4x+2=-1 | | X=15000+0.36(8600+0.2X) | | h+h+20=300 | | 3-(x-4)=4-(2x+5) | | 15-(-23)= | | 0=-x^2-9x+7 | | 28u^2-27u-10=0 | | .06(z-300)+.05z=.70z-205 | | 25+30=35+20 | | 0=x^4-4x^3-24x^2+20x+7 | | 5z(x-6y)+7(x-6y)=0 | | 3w-6=20 | | y=abs(4-x) | | -x^2-9x+7=0 | | 3(2x-8)-3=3(X-4)+6 | | x+(x-60)=180 | | x+4+2x+5=34 | | x(x-3)=(x-3) | | 9(11+6m)+9=216 | | 10-6-6n+15n=-2+12n+12 | | 110-290p=20 | | 6.3k-1.4+3.5=52.2 | | x(10x)=24 | | 138+167+133+14x+120+151+115+18x=1080 | | 4x+b=2x | | 138+167+133+14x+120+151+115+18x= |